A Documentary history of Communism in Russia : from Lenin to Gorbachev - Daniels, Robert V. (Robert Vincent), 1926-2010 (University of Vermont, Published by University Press of New England, 1993)
An extensive revision of the valued but unobtainable 1960 edition. Nearly 300 key documents are now readily available in translation.